2012
DOI: 10.1002/dc.22910
|View full text |Cite
|
Sign up to set email alerts
|

Eight cases of malignant mixed müllerian tumor (carcinosarcoma) of the uterus: Findings in surepath™ cervical cytology

Abstract: Malignant mixed Müllerian tumor (MMMT)/carcinosarcoma is a rare neoplasm of the female genital tract characterized by a mixture of epithelial and mesenchymal components. There are published reports of conventional cervical smear findings in uterine MMMT, but to the best of our knowledge the cytomorphology of MMMT in SurePath™ liquid-based cytology samples has not been described. We present a series of eight cases of uterine MMMT in SurePath™ cervical samples. The mean age of the women was 65.5 years (range, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Our case confirmed that the sarcomatous component does not shed easily, even in a case of predominant sarcoma on histology [18]. The presence of a sarcomatous component in a cervical Pap smear has also been identified as a characteristic feature [4,11]. …”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our case confirmed that the sarcomatous component does not shed easily, even in a case of predominant sarcoma on histology [18]. The presence of a sarcomatous component in a cervical Pap smear has also been identified as a characteristic feature [4,11]. …”
Section: Discussionsupporting
confidence: 64%
“…clusters of malignant epithelial cells in a necrotic background, were not evident or were not considered as such. Gupta et al [11 ]also reported that necrosis is not evident on liquid-based (SurePath) cytology. The introduction of LBC in cytology in recent years, and in particular in cervical cytology, represents a revolution in cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2, 3). Several other studies [6,8,19,20] and our observation show that the mesenchymal component is a rare finding in both liquid-based and conventional specimens, and only 2 of our study patients had malignant spindle cells on the Pap smears suggesting a biphasic tumor. …”
Section: Discussionmentioning
confidence: 69%
“…Earlier studies have described the cytological features of MMMTs based on conventional cervicovaginal cytology [6], but few studies have been published regarding findings on liquid-based Papanicolaou (Pap) smears [8]. …”
Section: Introductionmentioning
confidence: 99%